Strategies and knowledge sources in lexical inferencing through think-aloud : - Nguyễn, Thị Anh Thư (Can Tho University, 2008)
This study examines the use of strategies and knowledge sources in L2 lexical inferencing and their relationship with inferential success. The study also intends to find out if students' level of their reading proficiency would affect their successful inferencing.